Application and Effectiveness of IoT Edge and Fog Computing Technologies in Smart Energy Development with the Use of Encryption Algorithms and Security Systems - Wu, Wei (Computing and Informatics, 2024)
The invention of new technologies and the upgrading of existing ones to carry out assigned duties for human requirements efficiently and quickly are among the new prospects made possible by the evolution of artificial intelligence and information technology. This study aims to evaluate the performance of the Internet of Things solutions based on fog and edge computing. This article examines fog computing architectures and discusses the primary potential security and trust issues. The topical issue is to analyze and improve the security of data transmission from electronic devices and media in fog clouds using data encryption and encryption algorithms. The study confirms that depending on the amount of information to be processed, each block encryption algorithm can have a different key length. The study investigates the Advanced Encryption Standard (AES) algorithm as a more typical and efficient block encryption algorithm with key lengths of 128 and 256 bits. The paper contains a comparative characteristic of data processing speed with the size of 512 MB on the example of the AES and PRESENT block encryption algorithms, demonstrating an effective software implementation. The main scientific novelty of the study is that the efficiency of such coding algorithms as AES and PRESENT increases with a decrease in their size (from 256 to 128-bit and from 128 to 80-bit, respectively). It is necessary to expand our results for a more complex residential system.